Breathing exercise for hypertensive patients: A scoping review - Herawati, Isnaini; Mat Ludin, Arimi Fitri; M, Mutalazimah; Ishak, Ismarulyusda; Farah, Nor M. F. (Frontiers in Physiology, 2023)
Background Non-pharmacological management of hypertension includes weight loss, alcohol and sodium restriction, regular exercise, and relaxation. In people with overweight hypertension, systolic blood pressure (SBP) and diastolic blood pressure (DBP) can be decreased via exercise and weight loss together. Breathing exercises are one method of relaxing. Objectives The aim of this scoping review is to map the information that is currently available about the advantages of breathing exercises in decreasing blood pressure in hypertension patients. Methods This scoping review adheres to Arksey and O'Malley's framework, which entails identifying review questions, seeking pertinent evidence, choosing pertinent studies, mapping data, and discussing, concluding, and reporting the findings. The PRISMA flowchart is used to show how the evidence search process works. Results As a result, 339 articles in total were retrieved from the three databases. 20 papers total were included in this review after screening. In 14 of the 20 investigations, participants with stage 1 and stage 2 essential hypertension, two with pre-hypertension, and four with Isolated Systolic Hypertension (ISH) were studied. The respondents’ ages ranged from 18 to 75. The systolic blood pressure declined by 4 to 54.22 mmHg, while the diastolic blood pressure dropped by 3 to 17 mmHg. Conclusion Slow breathing can be used as an alternate, non-pharmacological therapy for hypertension individuals to reduce blood pressure.